2008
DOI: 10.4161/cc.7.16.6441
|View full text |Cite
|
Sign up to set email alerts
|

GFP reporter mice for the retinoblastoma-related cell cycle regulator p107

Abstract: The RB tumor suppressor gene is mutated in a broad range of human cancers, including pediatric retinoblastoma. Strikingly, however, Rb mutant mice develop tumors of the pituitary and thyroid glands, but not retinoblastoma. Mouse genetics experiments have demonstrated that p107, a protein related to pRB, is capable of preventing retinoblastoma, but not pituitary tumors, in Rb-deficient mice. Evidence suggests that the basis for this compensatory function of p107 is increased transcription of the p107 gene in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…28,29 It has been shown that, in the absence of pRb, negative cell growth genes, including other Rb family members, may be upregulated to compensate for pRb function. [30][31][32] Correlating with this, microarray analysis showed upregulation of Rbl1 (p107), Cdkn1a (p21 Cip1 ) and Cdkn2d (p19 Ink4d ) in the pRb -/-inner ear.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 It has been shown that, in the absence of pRb, negative cell growth genes, including other Rb family members, may be upregulated to compensate for pRb function. [30][31][32] Correlating with this, microarray analysis showed upregulation of Rbl1 (p107), Cdkn1a (p21 Cip1 ) and Cdkn2d (p19 Ink4d ) in the pRb -/-inner ear.…”
Section: Resultsmentioning
confidence: 99%
“…Mice were euthanized 3 days after the last injection. In unpublished observations related to a previous study (8), we found that injection of tamoxifen alone in Rosa26…”
Section: Rosa26mentioning
confidence: 92%
“…Finally, the Rb mRNA may be subject to posttranscriptional regulation that does not affect the eGFP mRNA, or the eGFP mRNA could be more stable than the Rb mRNA. We believe that a differential regulation of the Rb mRNA is more likely, because we recently described the use of a similar BAC transgenic reporter for the Rb family member p107 and did not observe any unusual stability or instability of the RNA from the same eGFP cassette in the liver or other organs (except the testes) of these transgenic mice (8). Posttranscriptional regulation of Rb may explain why eGFP is expressed at higher levels in the adult kidney than is Rb, as the eGFP transcript is missing any 3Ј UTR sequences that could be regulated by endogenous microRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations